Identification and characterization of sulfonyltransferases catalyzing ethyl sulfate formation and their inhibition by polyphenols - Stachel, Nicole; Skopp, Gisela (International journal of legal medicine, 2016)
Ethyl sulfate (EtS) is a minor metabolite of ethanol, usually being present along with ethyl glucuronide in both blood and urine. At present, there have been few studies on sulfotransferases (SULTs) catalyzing EtS formation. Moreover, inhibition by nutritional components on EtS formation, e.g., polyphenols that are extensively sulfonated, has not been addressed at all. Firstly, the incubation procedure was optimized with regard to buffer, substrate concentration, and incubation time. Recombinant SULT enzymes including SULT1A1, 1A3, 1B1, 1E1, and 2A1 were screened for their activity towards ethanol; subsequently, respective kinetics was investigated. The inhibitory potential of resveratrol, quercetin, and kaempferol being abundant in beer and wine was studied thereafter. Analysis was performed by liquid chromatography/tandem mass spectrometry (LC-MS/MS) using deuterated EtS as the internal standard. All enzymes are involved in the sulfonation of ethanol; respective kinetics followed the Michaelis-Menten model. Among the five SULTs under investigation, SULT1A1 displayed the highest activity towards ethanol followed by SULT2A1. Polyphenols significantly reduced the formation of EtS. Results revealed multiple SULT isoforms being capable of catalyzing the transfer of a sulfo group to ethanol; nevertheless, the relevance of SULTs’ polymorphism on the sulfonation of ethanol needs further appraisal. Nutritional components such as polyphenols effectively inhibit formation of EtS; this observation may partly serve as an explanation of the highly inter-individual variability of EtS findings in both blood and urine.
Published online: 14 February 2015
Gesehen am 12.05.2020